Alumina pellet carrier and its oil-ammonia column forming method

CN122957864APending Publication Date: 2026-10-23PETROCHINA CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510517262.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-23
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

另外,在滴球过程中,铝溶胶液滴进入油氨柱后,表面会包裹上油膜,影响铝溶胶与氨水接触反应,还会在下落时对铝溶胶液滴产生拖拽,影响成型载体的球形度

Benefits of technology

[0038]本发明提供的氧化铝小球载体的油氨柱成型方法,通过将稀硝酸缓慢滴加入拟薄水铝石混悬液中对拟薄水铝石进行酸化,有效控制拟薄水铝石的酸化程度,并提高拟薄水铝石酸化的均匀性,制备得到的铝溶胶具有优异的稳定性,可在长时间内进行连续滴球,使制备的小球载体具有高强度和高质量稳定性。结合滴球成型过程在漏斗形的成型柱中进行,加快油膜的脱落,使小球尽快发生凝胶反应,避免在下落过程中受到液体拖拽发生形变,保证小球载体具有良好的球形度,最终制备出质量稳定、强度高、球形度好的氧化铝小球载体。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005372894730000061
    Figure BDA0005372894730000061
  • Figure BDA0005372894730000071
    Figure BDA0005372894730000071
  • Figure HDA0005372894740000011
    Figure HDA0005372894740000011
Patent Text Reader

Abstract

The oil-ammonia column forming method of the alumina small ball carrier provided by the application controls the acidification degree of the pseudo-boehmite effectively and improves the uniformity of the pseudo-boehmite acidification by slowly adding dilute nitric acid into the pseudo-boehmite suspension to acidify the pseudo-boehmite. The prepared aluminum sol has excellent stability, can continuously drop the ball for a long time, and makes the prepared small ball carrier have high strength and high quality stability. The drop ball forming process is carried out in a funnel-shaped forming column, the oil film is accelerated to fall off, the small ball is gelled as soon as possible, the deformation caused by liquid drag during falling is avoided, the small ball carrier has good sphericity, and finally the alumina small ball carrier with stable quality, high strength and good sphericity is prepared.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to an oil-ammonia column forming method, specifically to an alumina microsphere carrier and its oil-ammonia column forming method. Background Technology

[0002] Droplet forming is a common method for preparing spherical alumina supports, including oil column forming, oil-ammonia column forming, and oil-water column forming. Compared with the traditional rolling spherical forming method, these methods have the advantages of high speed, high efficiency, and dust-free preparation. Among them, the oil-ammonia column forming method is carried out at room temperature, featuring low energy consumption and simple process. It uses boehmite as an alumina precursor, which is prepared into a colloidal powder-water mixture, i.e., alumina sol, by acid treatment. This alumina sol can gel under the action of ammonia. Utilizing this sol-gel process, alumina sol droplets are dropped into a system with an upper oil phase and a lower ammonia phase. After the droplets solidify, they form small spheres, which are then dried and calcined to obtain spherical alumina supports.

[0003] For example, Chinese patent document CN1493524A discloses a method for forming spherical alumina in an oil-ammonia column. This method involves dropping alumina sol into an oil-ammonia column composed of an upper oil phase (a low-viscosity organic substance) of 0.1–4.5 mm and a lower electrolyte solution phase (ammonia, ammonium sulfate, or ammonium chloride solution) of 10–300 cm to form spherical gel particles. The gel particles are then aged in the electrolyte solution phase, followed by drying and calcination. This method does not contain surfactants in the oil phase, resulting in spherical alumina with low impurity content.

[0004] Chinese patent document CN104891538A discloses a hydrothermally stable spherical alumina and its preparation method. The method employs an oil-ammonia column molding process, where a portion of boehmite is acidified to form a sol, and another portion is dispersed in water to form a suspension. The two are mixed to form a molding solution, which is then subjected to oil-ammonia column drop molding, aging, drying, and calcination to produce a spherical alumina carrier. The spherical alumina carrier prepared by this method exhibits excellent pore structure and a large specific surface area, as well as high hydrothermal stability.

[0005] Chinese patent document CN104418371A discloses a method for preparing spherical alumina. This method involves adding a mixed acid solution of organic and inorganic acids to boehmite powder to form an alumina sol, which is then dripped into an oil-ammonia column to form spheres. This method effectively reduces the bulk density of alumina spheres without the need for any pore-expanding agents, saving costs and simplifying subsequent processing steps.

[0006] In the preparation of alumina microsphere carriers using the oil-ammonia column molding method, the preparation of alumina sol is a crucial step, as its properties directly affect the molding effect and performance indicators of the microsphere carriers. If the acidification degree of the boehmite is not properly controlled, the prepared alumina sol will exhibit over-solution, resulting in excessive viscosity and poor flowability. To achieve continuous scale-up of the oil-ammonia column process, it is essential to ensure that the alumina sol maintains a stable and suitable viscosity over a long period, possessing a relatively long dropping window. Furthermore, during the dropping process, after the alumina sol droplets enter the oil-ammonia column, an oil film will form on their surface, affecting the contact reaction between the alumina sol and ammonia water. This oil film also drags the alumina sol droplets during their descent, affecting the sphericity of the formed carrier. Therefore, improving the stability of the alumina sol to enhance the dropping window and the sphericity of the carrier is of great significance for the preparation of alumina microsphere carriers using the oil-ammonia column molding method. Summary of the Invention

[0007] In view of this, the present invention provides an alumina microsphere carrier and a method for forming an oil-ammonia column thereof. The aluminum sol prepared by this method has stable properties, can prolong the dropping window period, and ensure the quality stability of the formed microspheres. At the same time, it effectively improves the sphericity of the alumina microsphere carrier, and prepares an alumina microsphere carrier with stable quality, high strength, and good sphericity.

[0008] To achieve the above objectives, the present invention adopts the following technical solution:

[0009] A method for forming an oil-ammonia column with an alumina microsphere carrier includes the following steps:

[0010] Under stirring, dilute nitric acid solution is added dropwise to the boehmite suspension to carry out a gelation reaction. The resulting alumina sol is then pelletized, aged, dried, and calcined to obtain alumina microsphere carriers.

[0011] Based on the total mass of the dilute nitric acid solution and the pseudoboehmite suspension as 100%, the nitric acid content is 0.2 wt% to 1 wt%.

[0012] The device used for drop ball forming includes a funnel-shaped forming column with openings at both the top and bottom, and a drip plate located above the forming column.

[0013] The forming column includes an upper section and a lower section connected by a ramp, and the diameter of the upper section is larger than that of the lower section; the forming column contains an immiscible upper oil phase and a lower water phase.

[0014] The drip tray is provided with drippers on the slope area corresponding to the slope, and the area of ​​the drip tray corresponding to the lower part of the forming column is not provided with drippers.

[0015] The aqueous phase includes ammonia and surfactants.

[0016] In one optional embodiment, the stirring speed is 30 to 100 r / min.

[0017] In one optional embodiment, the gelation reaction takes 1 to 5 hours.

[0018] In one optional embodiment, the nitric acid content in the dilute nitric acid solution is 1 wt% to 10 wt%.

[0019] In one optional embodiment, the dropping rate of the dilute nitric acid solution is 1 to 3 mL / min.

[0020] In one alternative embodiment, the aging process includes soaking the dripped microspheres in an aqueous phase, preferably for 0.5 to 3 hours.

[0021] In one optional embodiment, the drying temperature is 90–120°C and the time is 4–10 hours.

[0022] In one optional embodiment, the calcination temperature is 500–900°C and the time is 4–8 hours.

[0023] In one optional embodiment, the content of pseudoboehmite is 15wt% to 30wt%, based on the total mass of the dilute nitric acid solution and the pseudoboehmite suspension as 100%.

[0024] In one optional embodiment, the ammonia content in the aqueous phase is 1 wt% to 25 wt%.

[0025] In one optional embodiment, the surfactant is selected from at least one of cocamide, alkyl glucoside, alkyl alcohol polyether, fatty acid glycerides, polysorbate, and sorbitan oleate; preferably, the content of the surfactant in the aqueous phase is 1 wt% to 6 wt%. The surfactant reduces the interfacial tension between the oil and aqueous phases. Without a surfactant, the microspheres cannot overcome the oil-water interfacial tension and will remain at the interface, unable to enter the aqueous phase. However, too much surfactant should not be added to avoid problems such as interfacial emulsification and excessive foaming.

[0026] In one alternative embodiment, the oil phase is selected from at least one of diethyl ether, petroleum ether, hexane, heptane, octane, nonane, decane, undecane, dodecane, and white oil.

[0027] In one alternative embodiment, the angle between the ramp and the horizontal direction in the apparatus used for drop ball forming is 20° to 75°.

[0028] In one alternative embodiment, the height ratio of the lower section to the upper section in the apparatus used for drop ball forming is 1.5 to 66.

[0029] In one optional embodiment, the diameter ratio of the upper section to the lower section in the apparatus used for drop ball forming is 2 to 20.

[0030] In one optional embodiment, in the apparatus used for drop ball forming, the height of the oil phase is less than the height of the upper section; preferably, the height ratio of the oil phase to the upper section is 0.1 to 0.9.

[0031] In one optional embodiment, in the apparatus used for drop ball forming, the total height of the oil phase and the water phase is lower than the height of the forming column; preferably, the total height of the oil phase and the water phase differs from the height of the forming column by 0.5 to 3 cm.

[0032] In one alternative embodiment, the lower section of the device used for drop ball forming is connected to a pump to regulate the liquid level.

[0033] In one optional embodiment, in the device used for drop ball forming, the diameter of the drop plate is smaller than the diameter of the upper section, and the central area of ​​the drop plate corresponds to the central area of ​​the forming column; preferably, the diameter difference between the drop plate and the upper section is 0.5 to 1 cm.

[0034] In one optional embodiment, the device used for droplet forming has one, two, or more droplets; when there are two or more droplets, the droplets are evenly distributed and the distance between two adjacent droplets is 1 to 3 cm.

[0035] In one optional embodiment, in the device used for droplet forming, the height of the droplet from the oil phase surface in the forming column is 1 to 3 cm.

[0036] In one optional embodiment, in the device used for drop ball forming, the dripping speed of each dropper is 1 to 2 drops / second when the dripping plate is dripping the ball.

[0037] The present invention also provides an alumina microsphere carrier prepared by the above-mentioned oil-ammonia column molding method.

[0038] The oil-ammonia column forming method for alumina microsphere carriers provided by this invention involves slowly adding dilute nitric acid dropwise to a pseudoboehmite suspension to acidify the pseudoboehmite. This effectively controls the degree of acidification of the pseudoboehmite and improves the uniformity of acidification. The resulting alumina sol exhibits excellent stability and can be continuously dripped over a long period, resulting in a microsphere carrier with high strength and high quality stability. Furthermore, the dripping process is carried out in a funnel-shaped forming column, accelerating the shedding of the oil film and allowing the microspheres to gel quickly. This prevents deformation due to liquid drag during the drop, ensuring good sphericity of the microsphere carrier. Ultimately, this method produces alumina microsphere carriers with stable quality, high strength, and good sphericity. Attached Figure Description

[0039] Figure 1 This is a schematic diagram of the molding device used for drop ball molding provided by the present invention. Detailed Implementation

[0040] The present invention will now be described in detail through embodiments. It should be noted that the following embodiments are only for further illustration of the present invention and should not be construed as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments to the present invention based on the content of the present invention.

[0041] For experiments not specifically described in the examples, the procedures or conditions should be followed according to the conventional experimental procedures described in the literature in this field. Reagents or instruments whose manufacturers are not specified are all commercially available conventional reagent products.

[0042] Table 1

[0043]

[0044]

[0045] The sources of the above-mentioned raw materials are not intended to limit the present invention, and other commercially available raw materials can also meet the requirements for implementing the present invention.

[0046] Evaluation and analysis methods:

[0047] Viscosity was measured using a rotational viscometer, sphericity was determined using dynamic particle image particle size and shape analysis, and crushing strength was tested using a strength tester according to HG / T 2782-2024.

[0048] Example 1

[0049] Under stirring at 100 r / min, 400 g of boehmite powder was placed in 2160 g of deionized water and mixed to prepare a boehmite suspension.

[0050] Under stirring at 100 r / min, 107 g of 5% dilute nitric acid was added dropwise to the above pseudoboehmite suspension at a rate of 1 mL / min. After the addition was complete, stirring was continued for 4 h to form a uniform aluminum sol.

[0051] The above aluminum sol is attached Figure 1 Drop ball forming is performed in the forming apparatus shown. The resulting wet balls are aged in an aqueous phase for 2 hours. They are then removed, washed with water, drained, dried at 100°C for 5 hours, and calcined at 500°C for 6 hours to obtain alumina microsphere carriers.

[0052] in, Figure 1 The molding apparatus shown includes a funnel-shaped molding column with openings at both ends, and a drip tray located above the molding column. The molding column includes an upper section and a lower section connected by a ramp, with the diameter of the upper section being larger than that of the lower section. The molding column contains an upper oil phase and a lower water phase that are incompatible with each other. The drip tray has drippers on the slope area corresponding to the ramp, but no drippers are provided in the area of ​​the drip tray corresponding to the lower section of the molding column. The specific parameters of this molding apparatus can be selected according to the actual situation.

[0053] The molding device parameters used in this embodiment are as follows: the upper section is 2cm high and 30cm in diameter; the lower section is 132cm high and 10cm in diameter; the angle between the slope and the horizontal direction is 45°; the diameter of the dripping plate is 29cm, there are no drippers within a 10cm diameter area at the center of the dripping plate, and drippers are distributed every 2cm in the remaining area. The height of the dripper from the oil phase liquid surface is 3cm, and the dripping speed of each dripper is 1 drop / second when the dripping plate is dripping the ball.

[0054] The upper oil phase in the molding column is white oil with a height of 1.5 cm. The lower aqueous phase contains 1% ammonia and 1% cocoamide by mass. The total height of the oil and aqueous phases is 0.5 cm shorter than the height of the molding column. The lower section is connected to a pump for adjusting the liquid level.

[0055] The aluminum sol prepared above showed no significant changes after being sealed and left for 24 hours, and its viscosity remained essentially unchanged. The prepared alumina microsphere carriers were tested according to the aforementioned evaluation method. The average sphericity was 0.952, with 92% having a sphericity greater than 0.950; the average strength was 56 N / particle, with 95% having a strength between 50 and 60 N.

[0056] Example 2

[0057] Under stirring at 50 r / min, 200 g of boehmite powder was placed in 700 g of deionized water and mixed to prepare a boehmite suspension.

[0058] Under stirring at 50 r / min, 50 g of 10% dilute nitric acid was added dropwise to the above pseudoboehmite suspension at a rate of 1.5 mL / min. After the addition was complete, stirring was continued for 1 h to form a uniform aluminum sol.

[0059] The above-mentioned aluminum sol was drop-formed into balls in a molding device, and the resulting wet balls were aged in an aqueous phase for 0.5 hours. They were then removed, washed with water, drained, dried at 120°C for 4 hours, and calcined at 900°C for 4 hours to obtain the alumina microsphere carrier.

[0060] The molding apparatus used in this embodiment is similar to that in Embodiment 1, with the only difference being some parameters. The parameters of the molding apparatus used in this embodiment are as follows:

[0061] The upper section is 4cm high and 40cm in diameter; the lower section is 200cm high and 2cm in diameter; the angle between the slope and the horizontal direction is 20°; the diameter of the dripping tray is 39.5cm, with no drippers within a 2cm radius of the center, and drippers spaced 2cm apart in the remaining radius. The height of the drippers above the oil phase surface is 1cm, and the dripping speed of each dripper is 1 drop / second.

[0062] The upper oil phase of the molding column is hexane, with a height of 0.4 cm. The lower aqueous phase contains 6% ammonia and 3% alkyl glycosides by mass. The total height of the oil and aqueous phases is 1 cm shorter than the height of the molding column. The lower section is connected to a pump for level regulation.

[0063] The aluminum sol prepared above showed no significant changes after being sealed and left for 24 hours, and its viscosity remained essentially unchanged. The prepared alumina microsphere carriers were tested according to the aforementioned evaluation method. The average sphericity was 0.953, with 95% having a sphericity greater than 0.950; the average strength was 63 N / particle, with 93% having a strength between 60 and 70 N.

[0064] Example 3

[0065] Under stirring at 30 r / min, 200 g of boehmite powder was placed in 442 g of deionized water and mixed to prepare a boehmite suspension.

[0066] Under stirring at 30 r / min, 25 g of 8% dilute nitric acid was added dropwise to the above pseudoboehmite suspension at a rate of 2 mL / min. After the addition was complete, stirring was continued for 3 h to form a uniform aluminum sol.

[0067] The above-mentioned aluminum sol was drop-formed into balls in a molding device, and the resulting wet balls were aged in an aqueous phase for 3 hours. They were then removed, washed with water, drained, dried at 110°C for 6 hours, and calcined at 700°C for 5 hours to obtain the alumina microsphere carrier.

[0068] The molding apparatus used in this embodiment is similar to that in Embodiment 1, with the only difference being some parameters. The parameters of the molding apparatus used in this embodiment are as follows:

[0069] The upper section is 3cm high and 40cm in diameter; the lower section is 79.8cm high and 4cm in diameter; the angle between the slope and the horizontal direction is 75°; the diameter of the dripping tray is 39.3cm, with no drippers within a 4cm radius of the center, and drippers spaced 2cm apart in the remaining radius. The height of the drippers above the oil phase surface is 1.5cm, and each dripper delivers material at a rate of 2 drops / second when the dripping tray is used to deliver the ball.

[0070] The upper oil phase of the molding column is n-octane, with a height of 1.5 cm. The lower aqueous phase contains 15% ammonia and 6% alkyl alcohol polyether by mass. The total height of the oil and aqueous phases is 1 cm shorter than the height of the molding column. The lower section is connected to a pump for adjusting the liquid level.

[0071] The aluminum sol prepared above showed no significant changes after being sealed and left for 24 hours, and its viscosity remained essentially unchanged. The prepared alumina microsphere carriers were tested according to the aforementioned evaluation method. The average sphericity was 0.953, with 93% having a sphericity greater than 0.950; the average strength was 59 N / particle, with 93% having a strength between 55 and 65 N.

[0072] Example 4

[0073] Under stirring at 60 r / min, 200 g of boehmite powder was placed in 387 g of deionized water and mixed to prepare a boehmite suspension.

[0074] Under stirring at 60 r / min, 213 g of 3% dilute nitric acid was added dropwise to the above pseudoboehmite suspension at a rate of 3 mL / min. After the addition was complete, stirring was continued for 4 h to form a uniform aluminum sol.

[0075] The above-mentioned aluminum sol was drop-formed into balls in a molding device, and the resulting wet balls were aged in an aqueous phase for 2 hours. They were then removed, washed with water, drained, dried at 90°C for 10 hours, and calcined at 800°C for 6 hours to obtain the alumina microsphere carrier.

[0076] The molding apparatus used in this embodiment is similar to that in Embodiment 1, with the only difference being some parameters. The parameters of the molding apparatus used in this embodiment are as follows:

[0077] The upper section is 10cm high and 40cm in diameter; the lower section is 140cm high and 20cm in diameter; the angle between the slope and the horizontal direction is 60°; the diameter of the dripping tray is 39cm, with no drippers within a 20cm radius of the center, and drippers spaced 3cm apart in the remaining radius. The height of the drippers above the oil phase surface is 1cm, and each dripper delivers material at a rate of 2 drops / second when the dripping tray is used to deliver the ball.

[0078] The upper oil phase of the molding column is white oil, with a height of 9 cm. The lower aqueous phase contains 10% ammonia and 2% fatty acid glycerides by mass. The total height of the oil and aqueous phases is 1 cm shorter than the height of the molding column. The lower section is connected to a pump for adjusting the liquid level.

[0079] The aluminum sol prepared above showed no significant changes after being sealed and left for 24 hours, and its viscosity remained essentially unchanged. The prepared alumina microsphere carriers were tested according to the aforementioned evaluation method. The average sphericity was 0.952, with 94% having a sphericity greater than 0.950; the average strength was 82 N / particle, with 90% having a strength between 75 and 85 N.

[0080] Example 5

[0081] Under stirring at 80 r / min, 400 g of boehmite powder was placed in 1561 g of deionized water and mixed to prepare a boehmite suspension.

[0082] Under stirring at 80 r / min, 392 g of 6% dilute nitric acid was added dropwise to the above pseudoboehmite suspension at a rate of 2.5 mL / min. After the addition was complete, stirring was continued for 5 h to form a uniform aluminum sol.

[0083] The above-mentioned aluminum sol was drop-formed into balls in a molding device, and the resulting wet balls were aged in an aqueous phase for 1 hour. They were then removed, washed with water, drained, dried at 100°C for 6 hours, and calcined at 600°C for 7 hours to obtain the alumina microsphere carrier.

[0084] The molding apparatus used in this embodiment is similar to that in Embodiment 1, with the only difference being some parameters. The parameters of the molding apparatus used in this embodiment are as follows:

[0085] The upper section is 10cm high and 30cm in diameter; the lower section is 15cm high and 2cm in diameter; the angle between the slope and the horizontal direction is 60°; the diameter of the dripping tray is 29cm, with no drippers within a 2cm diameter area at the center of the tray, and drippers spaced 1cm apart in the remaining area. The height of the drippers from the oil phase surface is 1cm, and the dripping speed of each dripper is 2 drops / second when the dripping tray is used to drip the ball.

[0086] The upper oil phase of the molding column is dodecane, with a height of 7 cm. The lower aqueous phase contains 25% ammonia and 5% polysorbate by mass. The total height of the oil and aqueous phases is 3 cm shorter than the height of the molding column. The lower section is connected to a pump for adjusting the liquid level.

[0087] The aluminum sol prepared above showed no significant changes after being sealed and left for 24 hours, with its viscosity remaining essentially unchanged. The prepared alumina microsphere carriers were tested according to the aforementioned evaluation method. The average sphericity was 0.953, with 94% having a sphericity greater than 0.950; the average strength was 89 N / particle, with 92% having a strength between 85 and 95 N.

[0088] Comparative Example 1

[0089] This comparative example is similar to Example 1, except that the molding device and the method of adding the dilute nitric acid solution are different. In this comparative example, a cylindrical molding column is used, and the droppers on the dropping plate are evenly distributed on the dropping plate. Furthermore, the dilute nitric acid solution is directly added to the boehmite suspension. The preparation process of this comparative example includes the following steps:

[0090] Under stirring at 100 r / min, 400 g of boehmite powder was placed in 2160 g of deionized water and mixed to prepare a boehmite suspension.

[0091] Under stirring at 100 r / min, 107 g of 5% dilute nitric acid was directly added to the above pseudoboehmite suspension. After the addition was complete, stirring was continued for 4 h to form a uniform aluminum sol.

[0092] The above-mentioned aluminum sol was drop-formed into spheres using a cylindrical molding apparatus. The resulting wet spheres were aged in an aqueous phase for 2 hours. They were then removed, washed with water, drained, dried at 100°C for 5 hours, and calcined at 500°C for 6 hours to obtain the alumina microsphere carrier.

[0093] The molding apparatus parameters used in this comparative example are as follows: the total height of the cylindrical molding column is 1.44m; the diameter is 30cm; the diameter of the dripping plate is 29cm, and the drippers are evenly distributed on the dripping plate, with one dripper every 2cm. The height of the dripper from the oil phase surface is 3cm, and the dripping speed of each dripper is 1 drop / second. The upper oil phase in the molding column is white oil with a height of 1.5cm, and the lower aqueous phase contains 1% ammonia and 1% cocoamide by mass. The total height of the oil and aqueous phases is 0.5cm shorter than the height of the molding column. The lower section is connected to a pump for adjusting the liquid level.

[0094] The viscosity of the aluminum sol prepared above increased from 2051 mPa·s to 7567 mPa·s after being sealed and left for 30 minutes, and the fluidity deteriorated. The alumina microsphere carriers were tested according to the aforementioned evaluation method. The microsphere carriers were partially ellipsoidal in shape, with an average sphericity of 0.942 and an average strength of 38 N / particle.

[0095] Comparative Example 2

[0096] This comparative example is similar to Example 5, except that the molding device and the method of adding the dilute nitric acid solution are different. In this comparative example, a cylindrical molding column is used, and the droppers on the dropping plate are evenly distributed on the dropping plate. Furthermore, the dilute nitric acid solution is directly added to the boehmite suspension. The preparation process of this comparative example includes the following steps:

[0097] Under stirring at 80 r / min, 400 g of boehmite powder was placed in 1561 g of deionized water and mixed to prepare a boehmite suspension.

[0098] Under stirring at 80 r / min, 392 g of 6% dilute nitric acid was directly added to the above-mentioned boehmite suspension. After the addition was complete, stirring was continued for 5 h to form a uniform aluminum sol.

[0099] The above-mentioned aluminum sol was drop-formed into balls in a molding device, and the resulting wet balls were aged in an aqueous phase for 1 hour. They were then removed, washed with water, drained, dried at 100°C for 6 hours, and calcined at 600°C for 7 hours to obtain the alumina microsphere carrier.

[0100] The molding apparatus parameters used in this comparative example are as follows: the total length of the cylindrical molding column is 49.5 cm; the diameter is 30 cm; the diameter of the dripping plate is 29 cm, and the drippers are evenly distributed on the dripping plate, with one dripper every 1 cm. The height of the dripper from the oil phase surface is 1 cm, and the dripping speed of each dripper is 2 drops / second. The upper oil phase in the molding column is dodecane, with a height of 7 cm, and the lower aqueous phase contains 25% ammonia and 5% polysorbate by mass. The total height of the oil and aqueous phases is 3 cm shorter than the height of the molding column, and the lower section is connected to a pump for adjusting the liquid level.

[0101] The viscosity of the aluminum sol prepared above increased from 3234 mPa·s to 8467 mPa·s after being sealed and left for 30 minutes, and the fluidity deteriorated. The alumina microsphere carriers were tested according to the aforementioned evaluation method. The microsphere carriers were partially ellipsoidal in shape, with an average sphericity of 0.941 and an average strength of 58 N / particle.

[0102] The results of Example 1 and Comparative Example 1, and Example 5 and Comparative Example 2 show that the method of preparing alumina microsphere carrier by oil-ammonia column of the present invention can maintain the stability of the properties of the prepared alumina sol over a long period of time. The prepared alumina microsphere carrier has high strength and good sphericity, and the sphericity and strength distribution is concentrated, indicating that the quality of the microsphere carrier is stable.

[0103] Of course, the present invention may have other various embodiments. Without departing from the spirit and essence of the present invention, those skilled in the art can make various corresponding changes and modifications according to the present invention, but these corresponding changes and modifications should all fall within the protection scope of the claims of the present invention.

Claims

1. A method for forming an oil-ammonia column with an alumina microsphere carrier, characterized in that, Includes the following steps: Under stirring, dilute nitric acid solution is added dropwise to the boehmite suspension to carry out a gelation reaction. The resulting alumina sol is then pelletized, aged, dried, and calcined to obtain alumina microsphere carriers. Based on the total mass of the dilute nitric acid solution and the pseudoboehmite suspension as 100%, the nitric acid content is 0.2 wt% to 1 wt%. The device used for drop ball forming includes a funnel-shaped forming column with openings at both the top and bottom, and a drip plate located above the forming column. The forming column includes an upper section and a lower section connected by a ramp, and the diameter of the upper section is larger than that of the lower section; the forming column contains an immiscible upper oil phase and a lower water phase. The drip tray is provided with drippers on the slope area corresponding to the slope, and the area of ​​the drip tray corresponding to the lower part of the forming column is not provided with drippers. The aqueous phase includes ammonia and surfactants.

2. The method for forming an oil-ammonia column with an alumina microsphere carrier as described in claim 1, characterized in that, The nitric acid content in the dilute nitric acid solution is 1 wt% to 10 wt%.

3. The method for forming an oil-ammonia column with an alumina microsphere carrier as described in claim 1, characterized in that, The dropping rate of the dilute nitric acid solution is 1–3 mL / min.

4. The method for forming an oil-ammonia column with an alumina microsphere carrier as described in claim 1, characterized in that, The aging process includes soaking the dripped microspheres in an aqueous phase, preferably for 0.5 to 3 hours; and / or The drying temperature is 90–120°C, and the time is 4–10 hours; and / or The roasting temperature is 500–900℃, and the time is 4–8 hours.

5. The method for forming an oil-ammonia column of alumina microsphere carrier as described in claim 1, characterized in that, Based on the total mass of the dilute nitric acid solution and the boehmite suspension being 100%, the content of boehmite is 15wt% to 30wt%. The ammonia content in the aqueous phase is 1 wt% to 25 wt%.

6. The method for forming an oil-ammonia column with an alumina microsphere carrier as described in claim 1, characterized in that, The surfactant is selected from at least one of cocamide, alkyl glucoside, alkyl alcohol polyether, fatty acid glycerides, polysorbate, and sorbitan oleate; preferably, the content of the surfactant in the aqueous phase is 1 wt% to 6 wt%.

7. The method for forming an oil-ammonia column with an alumina microsphere carrier as described in claim 1, characterized in that, The oil phase is selected from at least one of diethyl ether, petroleum ether, hexane, heptane, octane, nonane, decane, undecane, dodecane, and white oil.

8. The method for forming an oil-ammonia column with an alumina microsphere carrier as described in claim 1, characterized in that, The angle between the slope and the horizontal direction is 20° to 75°; and / or The diameter ratio of the upper segment to the lower segment is 2 to 20; and / or The height ratio of the lower section to the upper section is 1.5 to 66.

9. The method for forming an oil-ammonia column of alumina microsphere carrier as described in claim 1, characterized in that, The height of the oil phase is less than the height of the upper section; preferably, the height ratio of the oil phase to the upper section is 0.1 to 0.9; and / or The total height of the oil phase and the aqueous phase is lower than the height of the molding column; preferably, the difference between the total height of the oil phase and the aqueous phase and the height of the molding column is 0.5–3 cm; and / or The lower section is connected to a pump for regulating the liquid level; and / or The number of drippers is one, two, or more; when the number of drippers is two or more, the drippers are evenly distributed, and the distance between two adjacent drippers is 1 to 3 cm; and / or The distance between the dropper and the oil phase surface in the molding column is 1 to 3 cm.

10. The alumina microsphere carrier prepared by the oil-ammonia column forming method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Preparation method of spherical aluminum oxide

    CN104418371A

  • Hydrothermally-stable spherical gamma-Al2O3 and preparation method thereof

    CN104891538A

  • Oil ammonia column shaping method of spherical aluminium oxide

    CN1493524A